Next‐Generation Summative English Language Proficiency Assessments for English Learners: Priorities for Policy and Research. Issue 1 (4th April 2016) - Wolf, Mikyung Kim; Guzman‐Orth, Danielle; Hauck, Maurice Cogan
Abstract: This paper is the third in a series concerning English language proficiency (ELP) assessments for K–12 English learners (ELs). The series, produced from Educational Testing Service (ETS), is intended to provide theory‐ and evidence‐based principles and recommendations for improving next‐generation ELP assessment systems, policies, and practices and to stimulate discussion on better serving K–12 EL students. The first paper articulated a high‐level conceptualization of next‐generation ELP assessment systems (Hauck, Wolf, & Mislevy, 2016). The second paper addressed accessibility issues in the context of ELP assessments for ELs and ELs with disabilities (Guzman‐Orth, Laitusis, Thurlow, & Christensen, 2016). The fourth paper dealt with one of the major uses of ELP assessments—the initial identification and classification of ELs (Lopez, Pooler, & Linquanti, 2016). The present paper focuses on summative ELP assessments that states use for accountability purposes. Based on the conversation that took place at the K–12 ELP Assessment Working Meeting on summative ELP assessments, we identify critical policy and research issues. We also highlight the challenges associated with measuring ELP in a diverse group of EL students and recommend ways to embrace and support EL students through shared goals and active communication across federal agencies, state agencies, local agencies, researchers, and practitioners. Abstract : Report Number: ETS RR‐16–08